Diseño de un esquema de reconexión automática para alimentadores primarios en siete subestaciones tipo de la Empresa Eléctrica Quito S.A. - Vasco Molina, Jorge Patricio (2015)
This paper aims to serve as a document for the implementation of the system of reconnection in EEQ. Has become necessary in which to gather information about the failures raised in the specified evaluation period. The result would be to identify the number of failures that were cleared by the operation of the instantaneous overcurrent function in both phases and neutral primary feeders considered for undergraduate work. The design was oriented to seven type substations where you can find a variety of equipment and protective interruption. Which was necessary to identify the characteristics of equipment breakdown and settings overcurrent and under voltage, who owns the feeder to know the impact it could have the reconnection of the feeders. This could work on the design, to establish the number of reconnections that could have the feeder, the reconnection time it should have, that direct the type of equipment breakdown and the largest type of load served relationship. Part of the design is the intervention of control and protection circuits in each of the primary, in circuits opening, closing and locking. These must have a relationship with reclosing relay for the operation of reclosing. In different substations are installed relays FDI, in this case it is necessary to intervene in the operating logic also enable reclose function. In addition to link protection function whit reclosing relay. As in EEQ has a SCADA system is important to re-build the communication parameters IEC 618 050 to have alarms on consoles operation control center, it is necessary to reconfigure the protocol and update the gateway, which no remote control operation is affected and work on par with reconnection function enabled.